Some Properties of Generalized Feebly Closed Maps and Feebly Closed Maps - Ibraheem Ressan, Dalal (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
The main purpose of this paper is study and investigate some properties of generalized feebly closed maps and feebly closed maps ,we give several results about that by using some concepts of topological as feebly closed sets,feebly open sets,generalized feebly closed sets and feebly normal space.